Tourism and transport in the sharing economy : strategies for resource and service management - Zio????ko, Monika (Routledge studies in Central and Eastern European Business and Economics, 2025)
This book identifies the growing importance of the sharing economy and its practical applications in such areas of the economy as tourism, transportation, and micromobility. At the same time, it highlights the challenges and benefits of this modern form of resource and service management. While there is literature available on these issues, this book offers value in providing a synthetic and up-to-date approach to the topic.It recognizes the impact of the sharing economy on business models, consumer behavior, especially in the tourism market, and urban logistics and answers research questions such as what place sharing has in contemporary economic and consumer trends, how the sharing economy influences the changes in traditional business models, how business financing models are evolving in light of the sharing economy, and what role crowdfunding plays in the era of the sharing economy. It also examines how the sharing economy can contribute to meeting contemporary challenges.The book provides insights for academics, researchers, and students, as well as policymakers and practitioners, and, more importantly, for further scientific research.